2012
DOI: 10.2308/accr-50230
|View full text |Cite
|
Sign up to set email alerts
|

Audit Quality and the Trade-Off between Accretive Stock Repurchases and Accrual-Based Earnings Management

Abstract: We examine whether audit quality affects the trade-off between accrual-based and real earnings management. We hypothesize that firms motivated to manage earnings per share (EPS) to meet or beat consensus analysts' forecasts are more likely to engage in accretive stock repurchases (a form of real earnings management) when their ability to manage earnings through accruals is constrained by high audit quality. We find that firms with high audit quality are more likely to use accretive stock repurchases and less l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 45 publications
2
83
1
Order By: Relevance
“…Thus the result of this study is sensitive to the accrual models used. Previous studies have sugges-ted that the real transaction earnings management is not only limited to operating transactions, but can also be done in investing and financing activities, as well as other forms of activities (Xu, Taylor, and Dugan 2007;Burnett et al 2012). Further studies are expected to examine the real transactions of investment and financing apart from the operational activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus the result of this study is sensitive to the accrual models used. Previous studies have sugges-ted that the real transaction earnings management is not only limited to operating transactions, but can also be done in investing and financing activities, as well as other forms of activities (Xu, Taylor, and Dugan 2007;Burnett et al 2012). Further studies are expected to examine the real transactions of investment and financing apart from the operational activities.…”
Section: Discussionmentioning
confidence: 99%
“…Cohen et al (2008) found that after the passage of the SOX Act in the United States, the trend of real transactionbased earnings management is increasing, while accrual-based earnings management is decreasing. This is because in auditing financial statements, external auditors are more difficult to detect real transactions compared to accrual-based earnings management (Burnett et al 2012;Graham et al 2005). In addition, managers have limited flexibility in accruals manipulation if accruals have been done in the previous years (Barton and Simko 2002).…”
Section: Real Earnings Management In Operating Activities and Earningmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our study is relevant to research related to the differential use of accruals and real activities to manage earnings (Cohen et al, 2008;Burnett et al, 2012;Zang, 2012;Chan et al, 2014). Although firms can substitute real earnings management for accrual-based earnings management as monitoring increases (e.g., Cohen et al, 2008), intense, short-term performance pressure can also motivate managers to increase their use of both accruals and real earnings management.…”
Section: Introductionmentioning
confidence: 98%
“…Specifically, auditors can provide industry-related information as long as they possess engagement-specific expertise. Previous researchers have demonstrated that industry specialization is associated with higher quality financial reporting (Gul et al, 2009;Burnett et al, 2012;Hegazy et al, 2015) which tends to reduce uncertainty among debt market participants, thereby affecting rating decisions (Ashbaugh-Skaife et al, 2006;Alissa et al, 2013). Ferguson and Pündrich (2015) recently reported that assurance from industry specialists with regard to non-financial information is of considerable importance to investors.…”
Section: Innovative Capacitymentioning
confidence: 99%